A multi-technique study of "barrier layer" nano-porosity in Zr oxides during corrosion and hydrogen pickup using (S)TEM, TKD, APT and NanoSIMS - Hu, J; Aarholt, T; Setiadinata, B; Li, K; Garner, A; Lozano-Perez, S; Moody, M; Frankel, P; Preuss, M; Grovenor, C (Elsevier, 2019)
We have used (S)TEM, TKD, NanoSIMS and APT to study nano-porosity in the oxide grown on deuterated Zr-1.0Nb and Zr-2.5Nb alloys. A detailed analysis of “barrier layer” nano-porosity by TEM and TKD has revealed that the oxide grain structure is much more disorganised and the nano-porosity network better developed in the rapidly oxidising post-transition alloy. Direct observations of the trapped deuterium (D) distributions from NanoSIMS analysis also shows much more penetration of the oxide layer post-transition. APT analysis shows that there is Fe and D segregation to some of the oxide grain boundaries with occasional evidence of porosity containing trapped D and H. We conclude that interconnected porosity would offer a dominant pathway for the transport of hydrogenic species to the metal substrate during the aqueous corrosion of zirconium alloys in service.